Sedimentological signatures of the sub-Amery Ice Shelf circulation - Hemer, M.A.; Post, A.L.; O'Brien, P.E.; Craven, M.; Truswell, E.M.; Roberts, D.; Harris, P.T. (Antarctic Science, 2007)
Abstract Two sediment cores collected from beneath the Amery Ice Shelf, East Antarctica describe the physical sedimentation patterns beneath an existing major embayed ice shelf. Core AM01b was collected from a site of basal freezing, contrasting with core AM02, collected from a site of basal melting. Both cores comprise Holocene siliceous muddy ooze (SMO), however, AM01b also recovered interbedded siliciclastic mud, sand and gravel with inclined bedding in its lower 27 cm. This interval indicates an episode of variable but strong current activity before SMO sedimentation became dominant. 14 C ages corrected for old surface ages are consistent with previous dating of marine sediments in Prydz Bay. However, the basal age of AM01b of 28250 ± 230 14 C yr bp probably results from greater contamination by recycled organic matter. Lithology, 14 C surface ages, absolute diatom abundance, and the diatom assemblage are used as indicators of sediment transport pathways beneath the ice shelf. The transport pathways suggested from these indicators do not correspond to previous models of the basal melt/freeze pattern. This indicates that the overturning baroclinic circulation beneath the Amery Ice Shelf (near-bed inflow–surface outflow) is a more important influence on basal melt/freeze and sediment distributions than the barotropic circulation that produces inflow in the east and outflow in the west of the ice front. Localized topographic (ice draft and bed elevation) variations are likely to play a dominant role in the resulting sub-ice shelf melt and sediment distribution.